The Impact of incomplete contracts on economics - Aghion, Philippe (Oxford University Press, 2016)
"The 1986 article by Grossman and Hart "A Theory of Vertical and Lateral Integration" has provided a framework for understanding how firm boundaries are defined and how they affect economic performance. The property rights approach has provided a formal way to introduce incomplete contracting ideas into economic modeling. The Impact of Incomplete Contracts on Economics collects papers and opinion pieces on the impact that this property right approach to the firm has had on the economics profession. It shows that the impact has been felt sometimes in significant ways in a variety of fields, ranging from the theory of the firm and their internal organization to industrial organization, international trade, finance, management, public economy, and political economy and political science. Beyond acknowledging how the property rights approach has permeated economics as a whole, the contributions in the book also highlight the road ahead--how the paradigm may change the way research is performed in some of the fields, and what type of research is still missing. The book concludes with a discussion of the foundations of the property rights, and more generally the incomplete contracting, approaches and with a series of contributions showing how behavioral considerations may provide a new way forward"--Provided by publisher.